The new economics of outdoor recreation - Hanley, Nick.; Shaw, W. Douglass; Wright, Robert E., 1958-; Edward Elgar Publishing (Cheltenham ; Northhampton, Mass. : E. Elgar, 2003)
This innovative book presents a series of up-to-date analyses of the economics of outdoor recreation. The distinguished group of authors covers real-world recreation management issues and applies economic understanding to these problems. An extensive introduction by the editors details the historical background of economists' interests in this subject, and reveals how economics can provide practical insights into improving how we manage our natural recreation areas.
pt. 1. The mountains -- pt. 2. Forests -- pt. 3. Rivers and the sea.
Includes bibliographical references and index.
Keywords: Outdoor recreation -- Economic aspects; Outdoor recreation -- Environmental aspects; Econometrics; Electronic books